2008 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--3128
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Calibrated Peer Review To Enhance Technical Critiquing Skills In A Bioengineering Laboratory

Abstract: Engineering and Professional Communication at Rice University. She supports written, oral, and visual communication instruction in science and engineering courses. In addition to working with students, Dr. Volz has conducted communication seminars about oral presentations, interviewing, and technical poster design for the Texas Society of Professional Engineers and Baylor College of Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This study is motivated by work demonstrating the inclusive and effective nature of peer review, co-created rubrics, and standards-based grading. An earlier study showed a strong positive correlation between instructor review and peer review in a biomedical engineering laboratory, suggesting peer review could be an effective form of feedback [1]. Peer review also resulted in the perceived improvement of students' ability to critique.…”
Section: Introductionmentioning
confidence: 96%
“…This study is motivated by work demonstrating the inclusive and effective nature of peer review, co-created rubrics, and standards-based grading. An earlier study showed a strong positive correlation between instructor review and peer review in a biomedical engineering laboratory, suggesting peer review could be an effective form of feedback [1]. Peer review also resulted in the perceived improvement of students' ability to critique.…”
Section: Introductionmentioning
confidence: 96%